2014
DOI: 10.1002/jssc.201400442
|View full text |Cite
|
Sign up to set email alerts
|

Rapid analysis of three β‐agonist residues in food of animal origin by automated on‐line solid‐phase extraction coupled to liquid chromatography and tandem mass spectrometry

Abstract: An automated online solid-phase extraction with liquid chromatography and tandem mass spectrometry method was developed and validated for the detection of clenbuterol, salbutamol, and ractopamine in food of animal origin. The samples from the food matrix were pretreated with an online solid-phase extraction cartridge by Oasis MCX for <5 min after acid hydrolysis for 30 min. The peak focusing mode was used to elute the target compounds directly onto a C18 column. Chromatographic separation was achieved under gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…With this system, Mi et al . reached LQ in the range of 0.024–0.29 μg/kg with low ME being observed.…”
Section: Selected Applications Of Multidimensional Separations In Foomentioning
confidence: 95%
See 1 more Smart Citation
“…With this system, Mi et al . reached LQ in the range of 0.024–0.29 μg/kg with low ME being observed.…”
Section: Selected Applications Of Multidimensional Separations In Foomentioning
confidence: 95%
“…This aspect is certainly an advantage for multiresidual methods development with the limitation that these phases are usually designed for weak and strong basic, or weak or strong acid and neutral compounds. As an example of these phases employment in cleanup are Strata™‐X for the determination of multiclass residues of veterinary drugs in porcine and bovine muscle and Oasis® in determination of antibiotics in milk and β‐agonist residues in animal origin food . The use of different mechanisms for compounds separation certainly is an advantage for multiresidual methods, when compared to silica bonded to alkyl, phenyl and cyanopropyl groups aiming to separate different compounds class.…”
Section: Classical and New Materials Used In Multidimensional Sample mentioning
confidence: 99%
“…Regarding β-agonist residue analysis in food of animal origin, a very recent research work done so far and summarized in this particular review showed that these chemicals can be specifically and selectively analyzed by automated online SPE coupled to LC-tandem mass spectrometry [82]. Methods such as HPLC coupled with DAD have also been reported in the determination of ractopamine and clenbuterol residues in beef after using graphene oxide hollow-fiber solid-phase microextraction (HF-SPME) as a sample extraction technique [56].…”
Section: 32mentioning
confidence: 99%
“…β 2 ‐Agonists, such as salbutamol (SAL) and clenbuterol (CLE), are a class of veterinary drugs used in food‐producing animals to promote leanness of meat . The illegal abuse of β 2 ‐agonists in breeding is detrimental to both animal and human health by inducing heart palpitations, diarrhea, muscle tremors, and even malignant tumors .…”
Section: Introductionmentioning
confidence: 99%